Analysis of Factors Inhibiting the Development of the National Student Sports Olympiad at the Elementary School Level - Cahyati, Nurnisa; Fauzi, Rizal Ahmad; Alif, Muhammad Nur (Pusat Kajian Pendidikan Olahraga, Kesehatan, dan Rekreasi Jurusan Pendidikan Olahraga Fakultas Ilmu Keolahragaan Universitas Negeri Padang, 2026)
This study examines the factors influencing the implementation of the National Student Sports Olympiad (O2SN) coaching program at the elementary school level. The research addresses issues related to students’ low participation, inconsistent motivation, and various external constraints that hinder the effectiveness of sports coaching. The purpose of this study is to analyze both internal and external factors affecting the success of O2SN coaching. This research employed a qualitative case study approach, with data collected through interviews, observations, and documentation. The findings reveal five main factors influencing O2SN coaching: student motivation, social support, facilities and infrastructure, teacher competence, and school support. Among these, student motivation emerged as the most dominant factor, influenced by aspects such as interest, discipline, physical condition, and self-confidence. External factors, including limited facilities, inadequate social support from parents and the environment, and constraints in teacher competence, were found to hinder optimal implementation. Additionally, school policies and resource allocation play a significant role in supporting the sustainability of the program. Overall, the study highlights the importance of an integrated approach involving students, teachers, schools, and families to enhance the effectiveness of sports coaching programs and improve student achievement in O2SN.